Physical mechanisms of negative corona current pulse with secondary oscillation - Chyhin, V.I. (Condensed Matter Physics, 2002)
The detailed modelling of the negative corona current pulses including the secondary oscillation (SCO) has been realized, using the continuity differential equations for the fluxes of positive and negative ions and electrons, supplemented by the Poisson’s equation for an electrical field in a quasione-dimensional space, as the basis for the numerical computation. The analysis of the basic plasma functions behaviour applicable to the pulsing corona in Ar+O₂ and N₂+O₂ mixtures in the concentration region of O₂ from 2 · 10−3% to 0.04% has been carried out and the physical mechanisms of the secondary current oscillation have been grounded for the first time. Moreover, an effect of the photoprocesses on the parameters of the strikingly different pulses in Ar+O₂ and N₂+O₂ mixtures is estimated for the first time. It has been determined that the SCO is caused by the field intensity oscillation in the antiphase in the surface region and in the end of the sheath. The SCO pulse can transfer into the full modes of the Trichel’s pulse. Characteristics of the “precursor” and the “step” in the leading pulse front are determined by the dynamics of the volumetric charges in the sheath, whereas the SCO shape is determined by the variable flow of the positive ions to the cathode. In N₂+O₂ the ionization of O₂ molecules by the N₂∗emitted photons leads to the adequate current rise. Pulse trailing part duration and current value are operated by the O₂− ions collisions with the N₂∗ metastables. Such processes are slowed in Ar+O₂. Проведено детальне моделювання нерівноважних процесів у від’ємному коронному розряді, зокрема, імпульсів струму із вторинними осциляціями (ВОС) на основі числового розв’язання рівнянь неперервності для позитивних і негативних іонів та електронів, разом із рівнянням Пуассона для електричного поля в квазі-одномірному просторі. Проаналізовано поведінку основних функцій плазми пульсуючої корони у сумішах аргону з киснем та азоту з киснем в області концентрацій 2 * 10-3%-0.04%, що дало змогу вперше обгрунтувати фізичні механізми зародження і розвитку ВОС. Виявлено, що три типи ВОС можуть існувати у різних часових інтервалах імпульсу. Встановлено, що вони є результатом коливання в антифазі напруженості поля в приповерхневій області та в кінці прикатодної оболонки. Характеристики “прекусора” і “сходинки” на провідному фронті імпульсу визначаються динамікою об’ємних зарядів в оболонці, тоді як форма ВОС задається змінним потоком позитивних іонів на катод. Додатково, вперше оцінено впливи фотопроцесів на параметри різко відмінних імпульсів у досліджених сумішах газів. В N₂+0₂ іонізація молекул 0₂ фотонами, емітованими збудженими молекулами N₂ приводить до адекватного росту пікового струму. Тривалість і значення струму у хвостовій частині імпульсу задається зіткненнями іонів О₂- із метастабілями N₂. У суміші Аг+0₂ такі процеси є слабими.